The Effectiveness of Dadap Serep Leaves in Reducing Baby's Body Temperature Post-Immunization - Sari, Selvi Puspan; Husnaini, Zihan; Fitria, Aida; Sumanti, Reni (International Journal of Nursing Information, 2023)
When seeing a baby with a fever, no mother doesn't panic. After immunization for babies, fever is something mothers don't want and worry about. Post-immunization in the form of vaccines, injection reactions, pharmacological effects, procedural errors, incidents, or other causal relationships that cannot be determined. One non-pharmacological solution is Dadap Serep Leaves (Erythrina Subumbrans). The research aimed to evaluate the effectiveness of Dadap Serep leaves in reducing the baby's body temperature after immunization. This research method is pre-experimental through a one-group pretest-posttest design. The research location is in the Posyandu Sei Renggas working area, Asahan Regency, Medan, Indonesia. The sampling technique used purposive sampling with a sample size of 60 respondents, data analysis used the Chi-Square test. The study's results showed a significant difference in the baby's body temperature after immunization after being treated with samples of Dadap Serep leaves. These results mean that Dadap Serep leaves effectively reduce the baby's body temperature after immunization. This research contributes scientific evidence about the benefits of Dadap Serep Leaves. Apart from that, it is one strategy to reduce the baby's body temperature when they have a fever, both post-immunization and other conditions.